2010
DOI: 10.1073/pnas.1007653107
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of 2-oxoglutarate signaling by the Synechococcus elongatus P II signal transduction protein

Abstract: P II proteins control key processes of nitrogen metabolism in bacteria, archaea, and plants in response to the central metabolites ATP, ADP, and 2-oxoglutarate (2-OG), signaling cellular energy and carbon and nitrogen abundance. This metabolic information is integrated by P II and transmitted to regulatory targets (key enzymes, transporters, and transcription factors), modulating their activity. In oxygenic phototrophs, the controlling enzyme of arginine synthesis, N-acetyl-glutamate kinase (NAGK), is a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
160
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(167 citation statements)
references
References 37 publications
7
160
0
Order By: Relevance
“…2a): from one subunit, Arg38 and Gln39 residues (belonging to the basal part of the T-loop) contact the c-phosphate of ATP, whereas Lys90 and Gly89 contact the b-and a-phosphate; from the opposite subunit, two Arg residues (101 and 103) of the C-loop contact c-and b-phosphates, whereas Thr29 and Val64 coordinate the adenosine moiety. The mode of 2-oxoglutarate binding to PII has been clarified recently by solving the crystal structures of PII proteins with Mg-ATP and 2-OG from the archaeon Archaeoglobus fulgidus (Maier et al 2011), the proteobacterium Azospirillum brasiliense (Truan et al 2010), and the cyanobacterium S. elongatus (Fokina et al 2010a). In the latter case, a snapshot of the sequential anticooperative binding of 2-OG to the three sites could be obtained.…”
Section: Pii-like Proteins: Witnesses Of a Widely Distributed Signalmentioning
confidence: 99%
“…2a): from one subunit, Arg38 and Gln39 residues (belonging to the basal part of the T-loop) contact the c-phosphate of ATP, whereas Lys90 and Gly89 contact the b-and a-phosphate; from the opposite subunit, two Arg residues (101 and 103) of the C-loop contact c-and b-phosphates, whereas Thr29 and Val64 coordinate the adenosine moiety. The mode of 2-oxoglutarate binding to PII has been clarified recently by solving the crystal structures of PII proteins with Mg-ATP and 2-OG from the archaeon Archaeoglobus fulgidus (Maier et al 2011), the proteobacterium Azospirillum brasiliense (Truan et al 2010), and the cyanobacterium S. elongatus (Fokina et al 2010a). In the latter case, a snapshot of the sequential anticooperative binding of 2-OG to the three sites could be obtained.…”
Section: Pii-like Proteins: Witnesses Of a Widely Distributed Signalmentioning
confidence: 99%
“…The nucleotide binding sites are mainly formed by the B-and C-loops from opposing subunits; ADP and ATP can occupy these sites competitively (4,6). The recent structures of Azospirillum brasilense GlnZ (7) and of Synechococcus elongatus P II (8) revealed that the P II 2-OG binding site is also located in the intersubunit cleft adjacent to the nucleotide binding pocket.…”
mentioning
confidence: 99%
“…P II contains three binding sites (one per subunit) for 2-OG and ATP (6,7), and it regulates the activity of N-acetyl-glutamate-kinase (NAGK), a key enzyme for biosynthesis of arginine, by direct protein-protein interactions (3,8,9). The 2-OG stimulates binding of NtcA to target sites (10), transcription activation in vitro (11), and complex formation between NtcA and PipX (12).…”
mentioning
confidence: 99%